Shallow geophysics of the Asinara Island Marine Reserve Area (NW Sardinia, Italy). Issue 2 (3rd July 2019) - Romeo, Roberto; Baradello, Luca; Blanos, Rita; Congiatu, Pietro Paolo; Cotterle, Diego; Ciriaco, Saul; Donda, Federica; Deponte, Michele; Gazale, Vittorio; Gordini, Emiliano; Lodolo, Emanuele; Paganini, Paolo; et al.
ABSTRACT: We present a high-resolution swath bathymetric and backscatter map of the entire sector of the Marine Reserve Area (MRA) of the Asinara Island, along with a geological and sediment thickness map derived from the interpretation of a large set of high-resolution seismic profiles, and an airborne-derived hyperspectral image of the Asinara Island. Acquired data show that most of the eastern marine sector of the Asinara Island is characterized by quite gentle bathymetric gradients, whereas the western coastline appears to be very indented, with an articulated and rough morphology of the seafloor, which deepens sharply towards the open sea. The maps presented in this study at the 1:50.000 scale do not only provide the first, high-resolution bathymetry of the MRA of the Asinara Island but also may furnish the base for the creation of a benthic habitat map and a more comprehensive maritime spatial planning of this protected area.